Long-Term Effects of Comprehensive Sex Education on Adolescent Decision-Making and Psychosocial Adjustment (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Comprehensive sex education aims to help youth gain a positive view of sexuality andappropriate knowledge to make healthy decisions about their sex lives. This report reviews CSE’s holisticapproach towards biological, psychological and social development. Relevant articles were gatheredfrom Google Scholar and PubMed search engines, after applying inclusion criteria and screening papers.CSE proved to reduce STDs, pregnancy, delay sex initiation and promote safe sex. The psychologicaloutcomes included decreased depression and increased self-esteem. CSE promoted healthyrelationships and reduced discrimination around sexual orientation. Therefore, CSE programs supportholistic youth development. This report recommends further research to correct inaccurate assumptionsand increase support for CSE programs. In order to prevent concerns such as unwanted pregnancies,sexually transmitted diseases, and sexual abuse, the health professionals have the ability to take on amore active role in the sexual education of the young people. At the same time, the promotion ofadolescents' sexual health may also be accomplished by improved personnel training, improvedknowledge, and improved organization of the health education services.